The Wounded Lion – Ageism and Masculinity in the Israeli Film Industry - Aharoni Lir, Shlomit; Ayalon, Liat (Frontiers in Psychology, 2022)
One of the intriguing issues connected to power relations in the world of cinema that has yet to be adequately explored is what has happened over the years concerning the dominance and privilege of masculinity as signifying preferred social status. This qualitative study explores this subject based on transcribed semi-structured interviews with 13 award-winning Israeli directors over the age of 55. The research examines two questions: How has the film industry changed its relation to leading, award-winning film directors as they grow older? And, what challenges confront the directors, in terms of their own self-perceptions? These questions capture the collisional intersection between hegemonic masculinity and ageism, because they examine the loss of power attributed to men in the film industry as they reach the second half of their lives. The findings led to the formation of a theoretical model of ageism within the cinematic industry, allowing for the dismantling of the different factors that create obstacles for directors as they get older. The four layers of the model are: arbitrary ageism, manifested in the demands of a rapidly changing industry in a changing world; passive ageism, expressed through encounters with negative attitudes; active ageism, reflected in preventing older directors from receiving funding and from screening their films; and self-ageism, manifested in the directors’ attitudes toward themselves.